Devolution and Indonesia's new forestry law - Wollenberg, Eva Karoline; Kartodihardjo, H. (Resources for the Future, Center for International Forestry Research (CIFOR) and Institute of Southeast Asian Studies (ISEAS), 2002)
Indonesia’s new basic forestry law makes some promising steps towards devolving control over forests to customary communities. This chapter analyzes the law’s provisions for new institutional arrangements, “customary communities” and co-operatives. The analysis shows how the extent of centralized control over these institutions potentially limits the law’s support for local management. Rights to local management under the new law are vulnerable to abuse if they are aquired by unintended parties. Empowerment of customary communities is constrained by the restrictions on economic rights. For devolution to occur, the implementing regulations should create legal possibilities for communities to manage with more certainty, to gain secure access to valuable economic benefits and to overcome conflicts with more powerful groups. A broader base of civil society organisational capacity and systematic checks and balances within government are necessary to support these changes.